2023
DOI: 10.1002/hbm.26408
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neurophysiology during nonword repetition in logopenic and non‐fluent variants of primary progressive aphasia

Abstract: Overlapping clinical presentations in primary progressive aphasia (PPA) variants present challenges for diagnosis and understanding pathophysiology, particularly in the early stages of the disease when behavioral (speech) symptoms are not clearly evident. Divergent atrophy patterns (temporoparietal degeneration in logopenic variant lvPPA, frontal degeneration in nonfluent variant nfvPPA) can partially account for differential speech production errors in the two groups in the later stages of the disease. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Phonological errors in non-word repetition correlated with metabolism in the posterior MTG and in the anterior fusiform gyrus. The posterior temporal lobe is a core component of the phonological loop [ 72 ] and is strictly related to phonological errors [ 73 ]. It is noteworthy that a recent study found decreased beta-band neural activity in lvPPA patients in the temporal lobe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phonological errors in non-word repetition correlated with metabolism in the posterior MTG and in the anterior fusiform gyrus. The posterior temporal lobe is a core component of the phonological loop [ 72 ] and is strictly related to phonological errors [ 73 ]. It is noteworthy that a recent study found decreased beta-band neural activity in lvPPA patients in the temporal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that a recent study found decreased beta-band neural activity in lvPPA patients in the temporal lobe. This reduction was associated with auditory encoding and may reflect the typical phonological processing deficit of these patients [ 73 ].…”
Section: Discussionmentioning
confidence: 99%